Integration of polarization in the LUTDavis model for optical Monte Carlo simulation in radiation detectors. (22nd October 2021) - Trigila, Carlotta; Roncali, Emilie
Abstract: Objective: Cerenkov photons have distinctive features from scintillation photons. Among them is their polarization: their electric field is always perpendicular to the direction of propagation of light and parallel to the plane of incidence. Scintillation photons are instead considered unpolarized. Approach: This study aims at understanding and optimizing the reflectance of polarized Cerenkov photons for optical Monte Carlo simulation of scintillation detectors with Geant4/GATE. First, the Cerenkov emission spectrum and polarization were implemented in the previously developed look-up-table Davis model of crystal reflectance. Next, we modified Geant4/GATE source code to account for scintillation and Cerenkov photons LUTs simultaneously. Then, we performed optical Monte Carlo simulations in BGO using GATE to show the effect of Cerenkov features on the photons' momentum at the photodetector face, using two surface finishes, with and without reflector. Main results: In this work, we describe the new features added to the algorithm and GATE. We showed that Cerenkov characteristics affect their probability to be reflected/refracted and thus their travel path within a material. Significance: We showed the importance of accounting for accurate Cerenkov photons reflectance while performing advanced optical Monte Carlo simulations.